The detrimental effect of donor-specific antibodies is irrespective of its level in highly-immunized living donor kidney transplant recipients: A case-control series - Tramper, T.; Roelen, D. L.; Brand-Schaaf, S. H.; Kal-van Gestel, J. A.; Kho, M. M. L.; Reinders, M. E. J.; Roodnat, J. I.; van de Wetering, J.; Betjes, M. G. H.; de Weerd, A. E. (Frontiers in Immunology, 2023)
Background The impact of donor-specific antibodies (DSA) in (highly-) immunized living donor kidney transplant recipients is reported differentially in various patient cohorts. Methods We have performed a retrospective analysis of all consecutive HLA-incompatible living donor kidney transplant recipients in our center between 2010-2019. Recipients who underwent plasmafiltration for a positive CDC-crossmatch were excluded. For each DSA+ recipient (DSA+), one immunized recipient without DSA (pPRA+) and two non-immunized recipients (pPRA-) were included. Patient and graft survival were analyzed and a subgroup analysis of DSA+ recipients was performed. Results For 63 DSA+ recipients, 63 PRA+ and 126 PRA- recipients were included. 26 (41%) had class I, 24 (38%) class II and 13 (21%) combined HLA class I and II DSA. Death-censored graft survival was inferior in DSA+ recipients compared to pPRA+ (HR 2.38 [95% CI 1.00-5.70]) as well as to pPRA- (HR 3.91 [1.86-8.22]). In multivariate analysis, DSA remained of negative influence on death-censored graft survival. Flowcytometric crossmatch, MFI value, HLA class and origin of DSA were not of significant impact. Conclusion In our cohort of (highly-) immunized recipients, pretransplant DSA led to inferior death-censored graft survival. There were no “safe” DSA characteristics since only DSA per se impacted death-censored graft survival.